Analysis of university students' participation in emergency education and its influencing factors in Shandong province - Jie, Du; Mengzhe, Yang; Huiwen, Luo; Junchang, Lin; Yuhui, Zhang (Frontiers in Public Health, 2023)
Objective The aim of this study is to understand the current situation of university students' participation in emergency education and its influencing factors in Shandong province, to improve the enthusiasm of university students' involvement in emergency training and exercise activities, and to provide a reference for universities to carry out education on public health emergencies. Methods From April to May 2020, 6,630 university students were selected from six universities in Shandong province by stratified random sampling. Descriptive analysis, χ2 test, and logistic regression for statistical analysis were also used. Results Overall, 35.5 and 55.8% of university students believed that it is necessary to participate in emergency education activities, and 65.8% of university students participated in emergency training and exercise activities. Through multivariate analysis, the results showed that university students who are men, sophomores, medical students, from within the province, the only child, have good health, take emergency education courses, think it is necessary to participate in emergency education, think the school attaches great importance to emergency education, believe that the professional teacher level to meet needs, know about public health emergencies, have received emergency education such as prevention and treatment of infectious diseases, and have a higher participation rate of emergency education and training activities. Conclusion The willingness of university students to participate in emergency education in Shandong province is high, but the willingness in emergency training and exercise activities is low. Gender, grade, profession, and students' nationalities, whether it is only children, health, the school courses in emergency education situations, the value of emergency education, emergency education to participate, the degree of teachers' professional level to meet the requirements, a public health emergency condition as well as the prevention and treatment of infectious diseases such as emergency education are the main influencing factors for university students' participation in emergency training and exercise activities in Shandong province.